2010
DOI: 10.21273/hortsci.45.11.1690
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Some Horticultural Traits in Walnut

Abstract: Correlation and causal relationships among 21 horticultural traits were determined using 71 walnut genotypes selected from seven valleys in Kerman Province, Iran. Pearson's correlation coefficient was calculated. Kernel percentage and blight susceptibility were used as dependent variables in a stepwise regression model to determine predictor variables. Direct and indirect effects of each independent variable were calculated using path analysis. A highly significant correlation was observed between late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 13 publications
6
31
0
Order By: Relevance
“…Because of the high heritability, fruit breeders are interested in pomological traits in walnut-breeding programs. However, knowledge of strong associations between pomological traits and other characteristics can guide appropriate selection schemes for walnut-breeding programs (Amiri et al, 2010). In this study, a significant and positive correlation was observed between nut and kernel weight and between both of them and NSI.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Because of the high heritability, fruit breeders are interested in pomological traits in walnut-breeding programs. However, knowledge of strong associations between pomological traits and other characteristics can guide appropriate selection schemes for walnut-breeding programs (Amiri et al, 2010). In this study, a significant and positive correlation was observed between nut and kernel weight and between both of them and NSI.…”
Section: Resultsmentioning
confidence: 53%
“…In addition, harvesting date had a significant negative correlation with kernel color. Yield (bearing) is the main objective of breeding programs of fruit trees including walnut (Amiri et al, 2010). A heat map of spearmen correlations between all measured traits, showed that bearing had a positive correlation with budbreak date, lateral bearing (P < 0.01), nut and kernel weight and NSI (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral bearing is a crucial trait in walnut breeding since it contributes to increased yield [42]. Fruiting at lateral positions on shoots was originally introduced into California from the cultivar 'Payne', which is in the background of all current varieties released by the Walnut Improvement Program of the University of California, Davis [4].…”
Section: Genetic Bases For the Expression Of Lateral Bearingmentioning
confidence: 99%
“…Additionally, recent studies have shown that shell thickness is significantly positively correlated with nut weight, which itself is significantly negatively correlated with kernel percentage (Arzani et al, 2008;Zhao et al, 2007). Shell thickness was one of the main variables accounting for kernel percentage and should be considered in breeding (Amiri et al, 2010). In addition, shell structural features such as shape, thickness, and texture, were the most important parameters affecting kernel extraction quality in nuts (Amiri et al, 2014;Ghafari et al, 2011).…”
mentioning
confidence: 99%